Optimization Techniques In PID Controller On A Nonlinear Electro-Hydraulic Actuator System - Ghazali, Rozaimi; Chai, Mau Shern; Chong, Shin Horng; Chong, Chee Soon; Jaafar, Hazriq Izzuan (Penerbit Akademia Baru, 2019)
The controller is an important component in the nonlinear control system, especially for the system that needs accuracy in position tracking. Electro-Hydraulic Actuator (EHA) system i s a popular nonlinear system that is used by researchers. Proportional- Integral-Derivative (PID) controller is the most popular controller that is normally used in the industry. This i s mainly because of i ts simplicity in the design process. However, there are three constants that need to be assigned in the PID controller, often we called thi s as the parameters s election process or the PID tuning process. In this paper, a comparison s tudy for the selection process of the PID parameters process will be conducted among Ziegler-Nichols tuning method, conventional Particle Swarm Optimization (PSO) technique and Priority-based Fitness Particle Swarm Optimization (PFPSO) technique. PFPSO is one of the improved versions of the conventional PSO technique. The s imulation study wi ll be conducted on a nonlinear Electro-Hydraulic Actuator (EHA) system. A simple robustness test on the PID controller will be evaluated in terms of actuator internal leakage. Results showed that the PID performed better whe n its controller's parameters are selected using PFPSO technique rather than the Ziegler-Nichols method and conventional PSO technique.